Helical Centerline Stent Improves Patency: Two-Year Results From the Randomized Mimics Trial. (June 2016) - Zeller, Thomas; Gaines, Peter A.; Ansel, Gary M.; Caro, Colin G.
Abstract : Background—: Reintervention in the femoropopliteal artery is frequent and a major driver of cost-effectiveness. High wall shear generated by swirling blood flow is associated with reduced occurrence of atherosclerosis and restenosis. This trial investigated the clinical and hemodynamic outcomes of the BioMimics 3D self-expanding tubular nitinol stent with helical centerline geometry compared with a straight stent in the femoropopliteal artery. Methods and Results—: In a prospective, multicenter, randomized controlled trial, 76 patients with symptomatic peripheral arterial disease were randomized 2:1 to receive a helical or a straight stent. An independent core laboratory adjudicated angiographic and ultrasound parameters. The primary safety end point was freedom from a composite of all death, target limb amputation, and target lesion revascularization at 30 days. The primary effectiveness end point was freedom from clinically driven target lesion revascularization at 6 months. Patency was a secondary end point. Subjects were followed up for 2 years from intervention. The primary safety (1-sided P <0.01) and efficacy (1-sided P <0.001) end points for the helical stent were met. The proportion of patients treated with the helical stent who maintained patency at 12 and 24 months was 80% and 72%, respectively, compared with 71% and 55% for the control group. The difference was significant through 24 months ( P =0.05). Freedom from clinically driven target lesion revascularization for the helical compared with straight stent was 91% versus 92% at 12 months and 91% versus 76% at 24 months. Conclusions—: Both groups had similar safety outcomes and clinically driven target lesion revascularization to 2 years. However, after placement of a BioMimics 3D helical stent, there was improved patency to 2 years. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02163863.